三角函式:1、兩角和公式sin(A+B)=sinAcosB+cosAsinBsin(A-B)=sinAcosB-sinBcosAcos(A+B)=cosAcosB-sinAsinBcos(A-B)=cosAcosB+sinAsinBtan(A+B)=(tanA+tanB)/(1-tanAtanB)tan(A-B)=(tanA-tanB)/(1+tanAtanB)cot(A+B)=(cotAcotB-1)/(cotB+cotA)cot(A-B)=(cotAcotB+1)/(cotB-cotA)2、倍角公式tan2A=2tanA/(1-tan2A) cot2A=(cot2A-1)/2cotacos2a=cos2a-sin2a=2cos2a-1=1-2sin2asinα+sin(α+2π/n)+sin(α+2π*2/n)+sin(α+2π*3/n)+……+sin[α+2π*(n-1)/n]=0cosα+cos(α+2π/n)+cos(α+2π*2/n)+cos(α+2π*3/n)+……+cos[α+2π*(n-1)/n]=0以及sin2 (α)+sin2(α-2π/3)+sin2(α+2π/3)=3/2tanAtanBtan(A+B)+tanA+tanB-tan(A+B)=03、·萬能公式:sinα=2tan(α/2)/[1+tan^2(α/2)]cosα=[1-tan^2(α/2)]/[1+tan^2(α/2)]tanα=2tan(α/2)/[1-tan^2(α/2)]4、半形公式sin(A/2)=√((1-cosA)/2) sin(A/2)=-√((1-cosA)/2)cos(A/2)=√((1+cosA)/2) cos(A/2)=-√((1+cosA)/2)tan(A/2)=√((1-cosA)/((1+cosA)) tan(A/2)=-√((1-cosA)/((1+cosA))cot(A/2)=√((1+cosA)/((1-cosA)) cot(A/2)=-√((1+cosA)/((1-cosA))5、和差化積2sinAcosB=sin(A+B)+sin(A-B) 2cosAsinB=sin(A+B)-sin(A-B)2cosAcosB=cos(A+B)-sin(A-B) -2sinAsinB=cos(A+B)-cos(A-B)sinA+sinB=2sin((A+B)/2)cos((A-B)/2 cosA+cosB=2cos((A+B)/2)sin((A-B)/2)tanA+tanB=sin(A+B)/cosAcosB tanA-tanB=sin(A-B)/cosAcosBcotA+cotBsin(A+B)/sinAsinB -cotA+cotBsin(A+B)/sinAsinB
三角函式:1、兩角和公式sin(A+B)=sinAcosB+cosAsinBsin(A-B)=sinAcosB-sinBcosAcos(A+B)=cosAcosB-sinAsinBcos(A-B)=cosAcosB+sinAsinBtan(A+B)=(tanA+tanB)/(1-tanAtanB)tan(A-B)=(tanA-tanB)/(1+tanAtanB)cot(A+B)=(cotAcotB-1)/(cotB+cotA)cot(A-B)=(cotAcotB+1)/(cotB-cotA)2、倍角公式tan2A=2tanA/(1-tan2A) cot2A=(cot2A-1)/2cotacos2a=cos2a-sin2a=2cos2a-1=1-2sin2asinα+sin(α+2π/n)+sin(α+2π*2/n)+sin(α+2π*3/n)+……+sin[α+2π*(n-1)/n]=0cosα+cos(α+2π/n)+cos(α+2π*2/n)+cos(α+2π*3/n)+……+cos[α+2π*(n-1)/n]=0以及sin2 (α)+sin2(α-2π/3)+sin2(α+2π/3)=3/2tanAtanBtan(A+B)+tanA+tanB-tan(A+B)=03、·萬能公式:sinα=2tan(α/2)/[1+tan^2(α/2)]cosα=[1-tan^2(α/2)]/[1+tan^2(α/2)]tanα=2tan(α/2)/[1-tan^2(α/2)]4、半形公式sin(A/2)=√((1-cosA)/2) sin(A/2)=-√((1-cosA)/2)cos(A/2)=√((1+cosA)/2) cos(A/2)=-√((1+cosA)/2)tan(A/2)=√((1-cosA)/((1+cosA)) tan(A/2)=-√((1-cosA)/((1+cosA))cot(A/2)=√((1+cosA)/((1-cosA)) cot(A/2)=-√((1+cosA)/((1-cosA))5、和差化積2sinAcosB=sin(A+B)+sin(A-B) 2cosAsinB=sin(A+B)-sin(A-B)2cosAcosB=cos(A+B)-sin(A-B) -2sinAsinB=cos(A+B)-cos(A-B)sinA+sinB=2sin((A+B)/2)cos((A-B)/2 cosA+cosB=2cos((A+B)/2)sin((A-B)/2)tanA+tanB=sin(A+B)/cosAcosB tanA-tanB=sin(A-B)/cosAcosBcotA+cotBsin(A+B)/sinAsinB -cotA+cotBsin(A+B)/sinAsinB